(untitled) (Vietnam Journal of Community Medicine, 2026)
Background: Calcifying fibrous tumor is a rare benign mesenchymal tumor that can occur in various organs but is uncommon in the stomach. The clinical, endoscopic and radiologic features of calcifying fibrous tumor are nonspecific and may mimic other gastric submucosal tumors, particularly gastrointestinal stromal tumor. Case presentation: We report the case of a 24-year-old female patient with an incidentally detected gastric lesion identified during upper gastrointestinal endoscopy. She underwent endoscopic submucosal dissection (ESD) for a gastric submucosal tumor. Histopathological examination demonstrated a well-circumscribed tumor composed of spindle cells arranged in short fascicles or whorled patterns within a densely hyalinized collagenous stroma, accompanied by lymphoplasmacytic infiltration and calcified deposits. No necrosis or increased mitotic activity was identified. Immunohistochemical staining showed that the tumor cells were negative for SMA, Desmin, CD117, DOG1, CD34, S100, and ALK-1, with a Ki67 labeling index of approximately 1%. Conclusion: This case contributes to the limited literature on gastric calcifying fibrous tumor, a rare benign mesenchymal neoplasm. Recognition of its characteristic histopathological features and immunohistochemical profile is essential for establishing an accurate diagnosis and differentiating it from other gastric mesenchymal neoplasms